Perancangan Interior Hotel bagi Kaum Difabel dengan Prinsip Desain Universal dan Inklusif di Surabaya - Aurellia Eunice Wahono; Cok Gede Padmanaba; Diana Thamrin (Intra, 2017)
People with Disabilities (PwD) are those with different physical, cognitive, mental, or emotional abilities. As stated in Indonesian Act no. 8 of 2016 that every disabled person has the rights in all aspects of life including tourism. The number of PwD is increasing in Indonesia, but it is not balanced with the availability of accessible public buildings. One of the public buildings that was highlighted is hotel, as a public accommodation facility in the city. The number of disabled friendly hotels in Indonesia is very low according to survey results by agoda.com. In the problem solving process, universal-inclusive design principles and accessible design standards are used as design concept. The universal design principles are applied in all aspect of design considerations to create an accessible and universal hotel. Design is limited and focused on the areas or facilites for hotel guests as a users and the hotel building is located in Surabaya. From the design result, it can be concluded that the principles of universal and inclusive design is the only solution in realizing an accessible hotel design. It is hoped that this design will become information and ispiration for interior design practitioners about the importance of universal-inclusive design that will help in improving the PwD’s prosperity now and in the future.